Science in painted body (editorial) - Roberto Polanco-Carrasco (CAEN, 2012)
The road is not easy and not necessarily popular, like the work of Robert Edward., For successful, we must rely on the firm belief that we are moving in the right direction and further that only insofar as we work so generous and together we can move beyond petty and always reach the questioned (but necessary)impact factor.The cover of this issue is dedicated to research, daring and teamwork, open and generous looking for body no longer like a taboo, and we seek that science no longer has seen as something alien and even immoral in the practice of psychology